A state-of-art review on 2D material-boosted metal oxide nanoparticle electrodes: Supercapacitor applications. (15th August 2023) - Sahoo, B.B.; Pandey, V.S.; Dogonchi, A.S.; Mohapatra, P.K.; Thatoi, D.N.; Nayak, N.; Nayak, M.K.
Abstract: Nanocomposite electrodes containing various dimensional structures of nanomaterials usually exhibit superior performances in supercapacitor applications because of their advantages on greater specific surface area, directional ion diffusion/charge transport roots, and structural durability etc. The novelty of the present study is that it reports recent advances of two-dimensional (2D) materials, such as graphene, MXene, transition metal dichalcogenides (TMDs), and layered double hydroxides (LDHs), used for boosting the performance of metal oxide-based electrode (e.g., RuO2, MnO2, NiO, Fe3 O4, Co3 O4 ) in supercapacitors applications. Herein, the constituents, structural features, electrochemical behavior and the nature properties of several metal oxide-based electrodes for supercapacitors are reviewed. The 2D material/metal oxide electrodes based supercapacitors have a high commercial potential due to their chemical stability, power and energy densities, specific capacitance, long cycle life, good electronic properties, and efficient ionic transport at the electrode-electrolyte interface as visualized. Finally, the future prospects and challenges for the development of 2D material/metal oxide nanocomposite electrodes in next generation supercapacitors have been summarized. Highlights: The 2D materials–metal oxide nanocomposites exhibit high specific capacity. They also exhibit high energy density, long lifespan, and better relative stability. Their microstructural changes accounts for manufacturing high performance SC. XRD, FESEM, TEM, XPS, RAMAN are executed. CV, GCD, EIS are analyzed. Future perspectives of the 2D materials–metal oxide nanocomposites are mentioned.